2014
DOI: 10.1105/tpc.114.123307
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisCuticular Wax Biosynthesis Is Negatively Regulated by theDEWAXGene Encoding an AP2/ERF-Type Transcription Factor  

Abstract: The aerial parts of plants are protected from desiccation and other stress by surface cuticular waxes. The total cuticular wax loads and the expression of wax biosynthetic genes are significantly downregulated in Arabidopsis thaliana under dark conditions. We isolated Decrease Wax Biosynthesis (DEWAX), which encodes an AP2/ERF-type transcription factor that is preferentially expressed in the epidermis and induced by darkness. Disruption of DEWAX leads to an increase in total leaf and stem wax loads, and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
156
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(165 citation statements)
references
References 71 publications
9
156
0
Order By: Relevance
“…Recently, At5g61590, a member of AP2/ERF family and an orthologue of MtSERF1, which is involved in SE induction in M. truncatula, was identified as being a direct target of AGL15 (Zheng et al 2013). It was shown that At5g61590 (DEWAX-Decrease Wax Biosynthesis) acts as a repressor of the biosynthesis of cuticular wax (Go et al 2014). In addition, the ethylene biosynthesis genes, ACC SYNTHASE (ACS) and ACC OXIDASE (ACO), are expressed in response to AGL15 (Zheng et al 2013).…”
Section: Se-related Functions Of Agl15mentioning
confidence: 99%
“…Recently, At5g61590, a member of AP2/ERF family and an orthologue of MtSERF1, which is involved in SE induction in M. truncatula, was identified as being a direct target of AGL15 (Zheng et al 2013). It was shown that At5g61590 (DEWAX-Decrease Wax Biosynthesis) acts as a repressor of the biosynthesis of cuticular wax (Go et al 2014). In addition, the ethylene biosynthesis genes, ACC SYNTHASE (ACS) and ACC OXIDASE (ACO), are expressed in response to AGL15 (Zheng et al 2013).…”
Section: Se-related Functions Of Agl15mentioning
confidence: 99%
“…In plants, ACL activity is correlated with lipid accumulation [86] and its mRNA levels coincide with peak cytosolic ACCase expression [87]. In addition, negative regulation of ACL subunit A (ACLA) reduced cuticular wax synthesis in epidermal cells of Arabidopsis [88], leading to the notion that increased acetyl-CoA supply in the cytosol may be to support the synthesis and elongation of long-chain FAs. Two species of microalgae, Nannochloropsis salina and Chlorella sp.…”
Section: Introductionmentioning
confidence: 99%
“…In Euphorbia suspension cells, light has been shown to affect the chain length distribution of the alkanes produced but alkane synthesis can occur in the dark (Carrière et al, 1990). In Arabidopsis (Arabidopsis thaliana), the total wax loads from stems and leaves were ;20% lower in plants grown in dark conditions for 6 d compared with those grown under long-day conditions (Go et al, 2014). An AP2/ERF-type transcription factor that is preferentially expressed in the epidermis and induced by darkness has been show to down-regulate the expression of alkane-forming enzymes.…”
Section: Microalgal Alka(e)ne Synthesis Requires Lightmentioning
confidence: 99%